Autoethnographic Projection of Climate Change Education through Project-Based Learning: Perspectives from Early Career Scholars - Zeeshan Faiez Siddique; Lizoon Nahar; Farheen Mahmood (Integrated Science Education Journal, 2025)
Purpose of the study: Project-based learning (PBL) is an effective pedagogical strategy for climate change education. This paper investigates the support early scholars receive and the challenges they face while conducting educational interventions using project-based learning (PBL) pedagogy for high school students’ environment and climate change education. Methodology: A collaborative autoethnographic approach was used to analyze the narratives from the projects conducted by two early scholars regarding their experiences educating high school students on environmental and climate education in Pittsburgh and Indiana, in Western Pennsylvania, US. Convenience sampling was used in this study. This research's primary data collection method includes personal narratives, reflective journals, and field notes accumulated throughout the project. A thematic deductive qualitative analysis was conducted. Main Findings: The findings demonstrate the effectiveness of PBL supported by institutional and community partnerships. The narratives reveal that universities and administrators have greater outreach capabilities than independent project leaders. Additionally, the study found that teachers’ contributions were instrumental in enhancing student engagement. Collaboration between local universities, schools, and community organizations creates opportunities for project leaders that might otherwise be challenging to access. Novelty/Originality of this Study: The study offers valuable strategies for project leaders to implement PBL successfully in diverse educational settings.